Bedsided Transcranial Sonographic Monitoring for Expansion and Progression of Subdural Hematoma Compared to Computed Tomography - Niesen, Wolf-Dirk; Rosenkranz, Michael; Weiller, Cornelius (Frontiers in Neurology, 2018)
Introduction Transcranial high-resolution ultrasonography reliably allows diagnosis and monitoring of intracerebral hemorrhage in adults. Sonographic monitoring of subdural hematoma (SDH) has not been evaluated in adults so far. This study investigates the reliability of transcranial gray-scale sonography (TGS) in monitoring acute and chronic SDH in adults. Methods TGS was performed in 47 consecutive patients with either acute or chronic SDH confirmed by cerebral CT. Four patients were excluded due to insufficient bone window. After identification of SDH in TGS extent was measured and correlated with extent of SDH on cerebral computer tomography (CCT). If possible measurement was performed at least on 2 days to evaluate the possibility to monitor SDH with TGS. Results In 43 patients with SDH, 76 examinations were performed with 2 examinations in 23 patients and 3 examinations in 10 patients. Overall extent of SDH correlated significantly between TGS and CCT (r = 0.962). Accordingly correlation was high during each single examination time point. In patients in need for surgical evacuation sonographic measurement yielded a sensitivity of 90.9% and specificity of 93.8% in predicting surgical evacuation (p < 0.001). Discussion Imaging of SDH with TGS is possible in patients with SDH and extent of SDH correlates significantly between TGS and CCT during initial as well as during follow-up examination. Thus monitoring of SDH with TGS at patients’ bedside is possible.